Preparation method of ultra-clear optical-grade polyester film
Polyethylene terephthalate slices were prepared by adding modified monomers into the esterification reactor, and combined with nano-scale opening agent and a special longitudinal pulling structure to form a polyester film with A/B/C three-layer structure, which solved the problem of poor transparency of the polyester film under strong light, and achieved high light transmittance, low haze and high definition.
Patent Information
- Application Number
- CN202411917327.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
AI Technical Summary
Existing polyester films are prone to fog or whitening in sunlight or strong light, resulting in poor clearness and poor feasibility of winding and slitting.
Polyethylene terephthalate slices were prepared by adding modified monomers into the esterification reactor, and polyester film with A/B/C three-layer structure was formed through a special longitudinal pulling structure design and the use of nano-scale opening agents.
It significantly improves the optical performance and transparency of the film, with light transmittance ≥90.0%, haze ≤0.8%, clarity ≥99.7%, and maintains A-level transparency under strong light, surpassing the existing optical film products on the market.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyester base film preparation, and in particular to a method for preparing an ultra-clear optical-grade polyester film. Background Art
[0002] BOPET polyester film has excellent properties such as high strength, heat resistance, and chemical corrosion resistance, and is widely used in food packaging, electronic products, industrial materials, building materials and other fields. Since PET optical polyester film also has the characteristics of high transparency, low haze, and high gloss, it is widely used in the electronics industry, such as for the manufacture of circuit boards, packaging of electronic components, flexible batteries, etc., which is conducive to the miniaturization, lightness, and efficiency of electronic products; in addition, optical-grade polyester base films have also been widely used in the construction and automotive industries, such as the manufacture of energy-saving glass, automotive window films, and automotive clothing. However, in actual applications, even polyester films with low haze will have obvious fogging or whitening under sunlight or strong light, making it difficult to achieve a very clear effect. For example, when driving at night, some low-haze window films also have the problem of limited driver vision due to fogging and whitening.
[0003] In order to better enhance the clarity of the film, existing patents mainly discuss how to reduce the haze of polyester film. For example, Chinese patent CN202210389816.2 discloses a low-haze polyester film and preparation method, which uses the method of adding two inorganic particles of different particle sizes to reduce the haze. However, the existing patents have not improved the clarity under strong light, such as fog points, that is, there is little research on further improving the visual effect of the film. Summary of the invention
[0004] The technical problem to be solved by the present invention is to provide a method for preparing an ultra-clear optical grade polyester film, so as to solve the problem that the polyester film in the prior art has low haze but poor visual clarity, has fog points or whitening, and poor feasibility of winding and slitting.
[0005] In order to solve the above technical problems, the technical solution of the present invention is: a method for preparing an ultra-clear optical grade polyester film, the innovation of which is: comprising the following steps: S1: preparing polyethylene terephthalate, adding terephthalic acid, ethylene glycol and various additives into an esterification reactor to prepare dihydroxyethyl terephthalate, and adding modified monomers into the esterification reactor at the same time, after esterification, preparing polyethylene terephthalate through polycondensation reaction, and obtaining optical grade polyethylene terephthalate slices, wherein the intrinsic viscosity of the polyethylene terephthalate slices is 0.60-0.75 dL / g, the melting point is 240-260°C, the mass fraction of diethylene glycol is 1-3%, and the terminal carboxyl content is 15-30 mol / t; S2: preparing an optical-grade nano-scale opening agent, selecting special particles and grinding them to obtain nano-scale particles, and then mixing them with a solvent to prepare a slurry, adding the prepared slurry into an esterification reactor, and adding a modified monomer into the esterification reactor, and granulating the nano-scale opening agent through esterification polymerization, wherein the nano-scale opening agent has an intrinsic viscosity of 0.60-0.75 dL / g, a melting point of 250-270°C, an L value of 30-80, a b value of 0-5, and a terminal carboxyl content of 15-30 mol / t; S3: The polyethylene terephthalate slices prepared in step S1 are sent to a vacuum hopper for dust removal, then to a static mixer, and then to a main extruder for melt extrusion at 265-295° C. to serve as an intermediate layer B for standby use; S4: sending the polyethylene terephthalate slices prepared in step S1 and the mixture of the nano-scale opening agent prepared in step S2 to two auxiliary extruders respectively, and performing melt extrusion at 265-295° C., wherein the material extruded by one auxiliary extruder is used as the upper surface layer A for standby use, and the material extruded by the other auxiliary extruder is used as the lower surface layer C for standby use; S5: passing the prepared middle layer B, upper surface layer A and lower surface layer C through a co-extrusion die, extruding them together through the die, and rapidly cooling them on a cold drum to form a cast sheet, which becomes a thick sheet with a three-layer structure of A / B / C. The cold drum temperature is 25-35° C., and the die lip opening of the co-extrusion die is set at 2-4 mm; S6: The casting sheet enters the longitudinal drawing machine from the longitudinal drawing entrance, is longitudinally stretched after preheating, and is cooled by the cooling roller to form a unidirectional sheet. The conveying speed of the casting sheet is set at 5-70m / min, the temperature of the preheating roller is set at 60-90℃, the stretching roller pressure of the longitudinal drawing machine is set at 2-8kg, the stretching temperature of the longitudinal drawing machine is set at 70-130℃, the infrared power of the longitudinal drawing machine is 40-60%, the longitudinal stretching ratio is 2.0-3.8, and the temperature of the cooling roller is set at 20-40℃; S7: The unidirectional sheet enters the horizontal stretching machine through the horizontal zipper clamp, and forms an optical-grade polyester base film after horizontal preheating, horizontal stretching, shaping and cooling. The conveying speed of the horizontal zipper clamp is 150-250 m / min, the temperature of the preheating section of the horizontal stretching machine is set at 100-130°C, the stretching temperature of the stretching section of the horizontal stretching machine is 110-150°C, the stretching ratio of the horizontal stretching machine is 3.0-4.5 times, the shaping temperature of the heat shaping section of the horizontal stretching machine is set at 220-245°C, and the cooling temperature of the horizontal stretching machine is set at 20-40°C; S8: After being horizontally stretched, the polyester base film enters the traction process for corona, thickness measurement, and defect detection, and is rolled up by a winding device to form a polyester base film mother roll; S9: The wound polyester base film mother roll enters the slitting device for slitting, and the slitting speed is 300~500m / min to obtain the ultra-clear optical grade polyester film.
[0006] Furthermore, in step S1, the various types of additives include one or more of a catalyst, a stabilizer, an antioxidant, a toner, an anti-ether agent, and a stabilizer; The catalyst is one or more of antimony trioxide, antimony glycol, aluminum trioxide, Ti series, germanium series, tin series, and cobalt series; The stabilizer is one or more of phosphoric acid, phosphorous acid, triphenyl phosphate, and triphenyl phosphite; The antioxidant is one or more of the hindered phenol antioxidants CHEMNOX1010, CHEMNOX1076, CHEMNOX1098, and CHEMNOXDLTP; The modified monomer is one or a combination of isophthalic acid and benzoate, and the added ratio of the modified monomer is 1-10% of the total mass.
[0007] Furthermore, in step S2, the special particles are one or more of silicon dioxide, silica gel fine powder, silicon microspheres, calcium carbonate, calcium sulfate, barium carbonate, barium sulfate, and hydrated magnesium silicate; The average diameter of the particles in the slurry is one or more of 20nm, 50nm, 100nm, 150nm, 200nm, 220nm, and 300nm; The shape of the particles in the slurry is one or more of spherical, columnar, rhombic, and amorphous; The ratio of particles to solvent in the slurry is: 0-100 parts by mass of inorganic particles mixed with 0-1000 parts by mass of solvent; The nano-scale opening agent is composed of 1% to 25% by mass of nano-slurry and 99% to 75% of copolyester with a molecular weight of 20,000 to 30,000; The modified monomer is an aliphatic diol copolymer monomer, one or more of 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol, and the modified monomer accounts for 2-4% of the solvent in the reactor.
[0008] Furthermore, the main extruder and the auxiliary extruder are both twin-screw extruders, and the twin-screw extruder is also equipped with a vacuum device, and the vacuum degree of the vacuum device is set to -10~4bar.
[0009] Furthermore, the mixture in the auxiliary extruder is composed of 95% to 50% by mass of polyethylene terephthalate chips and 5% to 50% by mass of nano-level opening agent.
[0010] Further, in step S6, the longitudinal stretching machine is composed of three parts: a preheating roller group, a stretching roller group, and a cooling roller group, wherein each roller of the preheating roller group is made of one or more of chrome-plated rollers, tungsten carbide, and aluminum oxide materials, and is driven by a motor; the stretching roller group is composed of three groups of stretching rollers, and infrared radiators are installed on the first two groups, and the rollers of the stretching group are made of one or more of chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor; the rollers of the cooling group are made of one or more of chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor; The longitudinal stretching adopts a three-point stretching method. The temperature of the first stretching is 70~90℃, infrared heating is set, and the stretching ratio is between 1.0~1.2; the temperature of the second stretching is 90~100℃, infrared heating is set, and the stretching ratio is between 1.2~1.7; the temperature of the third stretching is 100~130℃, without infrared heating, and the stretching ratio is between 1.7~2.
[0011] The advantages of the present invention are: the preparation method of the present invention, by adding modified monomers in the esterification reaction kettle, can not only change the crystallization speed of polyester, but also control the shape of crystals in the production process, so that the crystallization speed is slowed down and the crystal size is smaller, effectively reducing the fluorescence effect generated by light passing through the film surface, and can significantly improve the optical properties of the film from the core layer.
[0012] The preparation method of the present invention uses special opening agent particles and grinds the opening agent to a nanometer size. The size reduction can effectively reduce the obstruction of light, and at the same time control the shape of the opening agent to be regular. The opening agent is modified by a corresponding modified monomer to avoid agglomeration, and the aggregation of the opening agent generated in the extruder to form large-sized particles or crystals is effectively prevented, so that the optical performance and clarity of the film can be improved from the surface layer.
[0013] The preparation method of the present invention can achieve three-point stretching by designing a special longitudinal stretching structure, and can increase the stretching ratio by small proportions to increase the stretching speed, thereby accelerating the crystallization speed, but the crystal size is smaller, which can further ensure the optical properties and clarity of the film.
[0014] The preparation method of the present invention further improves the existing optical performance and effects. By adding special optical grade polyester chips to the core layer and modified nano-scale opening agents to the surface layer, and through a specific longitudinal pulling structure design, low haze and high clarity can be achieved. The transmittance is ≥90.0%, the haze is ≤0.8, the clarity is ≥99.7%, and the clarity grade under strong light or sunlight is A-level, and the clarity is higher than that of optical film products currently on the market.
[0015] The preparation method of the present invention, by matching a special longitudinal stretching design, only requires modification of the existing longitudinal stretching equipment, and has simple preparation process, strong operability, strong practicability and low cost. DETAILED DESCRIPTION
[0016] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation method, structure, characteristics and effects of the present invention are described in detail below in combination with the preferred embodiments.
[0017] The preparation method of the ultra-clear optical grade polyester film of the present invention is achieved by the following steps: S1: Preparation of polyethylene terephthalate. Adding terephthalic acid, ethylene glycol and various additives into an esterification reactor to prepare dihydroxyethyl terephthalate. Meanwhile, adding modified monomers into the esterification reactor. After esterification, polyethylene terephthalate is prepared through polycondensation reaction to obtain optical grade polyethylene terephthalate slices. The intrinsic viscosity of the polyethylene terephthalate slices is 0.60-0.75 dL / g, the melting point is 240-260°C, the mass fraction of diethylene glycol is 1-3%, and the terminal carboxyl content is 15-30 mol / t.
[0018] Various auxiliary agents include one or more of catalysts, stabilizers, antioxidants, toners, anti-ether agents, and stabilizers; the catalyst is one or more of antimony trioxide, ethylene glycol antimony, aluminum trioxide, Ti series, germanium series, tin series, and cobalt series; the stabilizer is one or more of phosphoric acid, phosphorous acid, triphenyl phosphate, and triphenyl phosphite; the antioxidant is one or more of hindered phenol antioxidants CHEMNOX1010, CHEMNOX1076, CHEMNOX1098, and CHEMNOX DLTP; the modified monomer is one or a combination of isophthalic acid and benzoate, and the added ratio of the modified monomer is 1-10% of the total mass.
[0019] Table 1 shows the polyethylene terephthalate slices prepared by using different ratios of the above steps:
[0020] Taking polyester 01 as an example, the intrinsic viscosity is 0.68dL / g, the melting point is 260℃, the mass fraction of diethylene glycol is 1.2%, and the terminal carboxyl content is 18 mol / t. This slice is reserved.
[0021] S2: prepare optical grade nano-scale opening agent, select special particles and grind them to obtain nano-scale particles, then mix them with solvent to prepare slurry, add the prepared slurry into esterification reactor, add modified monomer into esterification reactor at the same time, granulate through esterification polymerization to obtain nano-scale opening agent, the characteristic viscosity of nano-scale opening agent is 0.60-0.75dL / g, melting point is 250-270℃, L value is 30-80, b value is 0-5, and terminal carboxyl content is 15-30 mol / t.
[0022] The special particles are one or more of silicon dioxide, silica gel powder, silicon microspheres, calcium carbonate, calcium sulfate, barium carbonate, barium sulfate, and hydrated magnesium silicate; the average diameter of the particles in the slurry is one or more of 20nm, 50nm, 100nm, 150nm, 200nm, 220nm, and 300nm; the shape of the particles in the slurry is one or more of spherical, columnar, diamond-shaped, and amorphous; the ratio of particles to solvent in the slurry is: 0-100 parts by mass of inorganic particles mixed with 0-1000 parts by mass of solvent; the modified monomer is an aliphatic diol copolymer monomer, one or more of 1,3-propylene glycol, 1,4-butanediol, and 1,6-hexanediol, and the modified monomer accounts for 2-4% of the solvent in the reactor.
[0023] Table 2 is a table showing the dosage of nanomaterials used in the polishing slurry of Example No. "Slurry 01 to Slurry 07" in the above steps:
[0024] The modified monomer added to the esterification reactor is an aliphatic diol comonomer, one or more of 1,3-propylene glycol, 1,4-butylene glycol, and 1,6-hexanediol. The modified monomer accounts for 0.5-4% of the solvent in the reactor.
[0025] The dosage of the modified monomers of the nano-scale opening agent examples "Opening Agent 01 to Opening Agent 08" is shown in Table 3 below.
[0026]
[0027] The nano-scale opening agent is composed of 1% to 25% by mass of nano-slurry and 99% to 75% of copolyester with a molecular weight of 20,000 to 30,000.
[0028] S3: The polyethylene terephthalate slices prepared in step S1 are sent to a vacuum hopper for dust removal, then to a static mixer, and then to a main extruder for melt extrusion at 265-295° C. to be used as an intermediate layer B for standby use.
[0029] S4: The polyethylene terephthalate slices prepared in step S1 and the mixture of the nano-scale opening agent prepared in step S2 are respectively sent to two auxiliary extruders for melt extrusion at 265-295° C., wherein the material extruded by one auxiliary extruder is used as the upper surface layer A, and the material extruded by the other auxiliary extruder is used as the lower surface layer C.
[0030] Both the main extruder and the auxiliary extruder are twin-screw extruders, and the twin-screw extruder is also equipped with a vacuum device, and the vacuum degree of the vacuum device is set to -10~4bar.
[0031] The mixed material in the auxiliary extruder is composed of 95% to 50% by mass of polyethylene terephthalate chips and 5% to 50% by mass of nano-level opening agent.
[0032] S5: The prepared middle layer B, upper surface layer A and lower surface layer C are passed through a co-extrusion die, extruded together through the die, and rapidly cooled on a cold drum to form a cast sheet, which becomes a thick sheet with a three-layer structure of A / B / C. The cold drum temperature is 25-35°C, and the die lip opening of the co-extrusion die is set at 2-4mm.
[0033] S6: The casting sheet enters the longitudinal drawing machine from the longitudinal drawing entrance, is longitudinally stretched after preheating, and is cooled by cooling rollers to form unidirectional sheets. The conveying speed of the casting sheet is set at 5-70m / min, the temperature of the preheating roller is set at 60-90℃, the stretching roller pressure of the longitudinal drawing machine is set at 2-8kg, the stretching temperature of the longitudinal drawing machine is set at 70-130℃, the infrared power of the longitudinal drawing machine is 40-60%, the longitudinal stretching ratio is 2.0-3.8, and the temperature of the cooling roller is set at 20-40℃.
[0034] The longitudinal stretching machine consists of three parts: a preheating roller group, a stretching roller group, and a cooling roller group. The rollers of the preheating roller group are made of one or more materials selected from chrome-plated rollers, tungsten carbide, and aluminum oxide, and are driven by a motor. The stretching roller group consists of three groups of stretching rollers, and infrared radiators are installed on the first two groups. The rollers of the stretching group are made of one or more materials selected from chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor. The rollers of the cooling group are made of one or more materials selected from chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor. The longitudinal stretching adopts a three-point stretching method. The temperature of the first stretching is 70~90℃, infrared heating is set, and the stretching ratio is between 1.0~1.2; the temperature of the second stretching is 90~100℃, infrared heating is set, and the stretching ratio is between 1.2~1.7; the temperature of the third stretching is 100~130℃, without infrared heating, and the stretching ratio is between 1.7~2.
[0035] S7: The unidirectional sheet enters the horizontal stretching machine through the horizontal zipper clamp, and forms an optical-grade polyester base film after horizontal preheating, horizontal stretching, shaping and cooling. The conveying speed of the horizontal zipper clamp is 150~250m / min, the temperature of the preheating section of the horizontal stretching machine is set at 100~130℃, the stretching temperature of the stretching section of the horizontal stretching machine is 110~150℃, the stretching ratio of the horizontal stretching machine is 3.0~4.5 times, the shaping temperature of the heat setting section of the horizontal stretching machine is set at 220~245℃, and the cooling temperature of the horizontal stretching machine is set at 20~40℃.
[0036] S8: After being horizontally stretched, the polyester base film enters the traction process for corona, thickness measurement, and defect detection, and is rolled up by a winding device to form a polyester base film mother roll.
[0037] S9: The wound polyester base film mother roll enters the slitting device for slitting, and the slitting speed is 300~500m / min to obtain the ultra-clear optical grade polyester film.
[0038] Table 4 shows the optical grade polyester chips prepared in Example 1 and the nano-scale opening agent prepared in Example 2.
[0039] Table 5 tests the corresponding properties of Examples 1-1 to 1-8:
[0040] The preparation method of the polyester film of the comparative example is as follows: (1) One or more of the following: FG600-based film-grade polyester chips, FG604-based polyester chips, FG641-based polyester chips, EMT-8200 polyester chips, and EMT-8300 polyester chips provided by Sichuan Dongcai Technology Group Co., Ltd., are sent to a vacuum hopper, dusted, and then sent to a static mixer, and then sent to a main extruder as an intermediate layer B, and melt-extruded at 265-295°C.
[0041] (2) The mixture of the above-mentioned polyester chips and the commercially available anti-blocking agent is sent to the auxiliary extruder 1 as the upper surface layer A; the mixture of the above-mentioned polyester chips and the commercially available anti-blocking agent is sent to the auxiliary extruder 2 as the lower surface layer C, and melt extruded at 265-295°C.
[0042] (3) The above three layers of melt are passed through a co-extrusion die, extruded through the die head, and rapidly cooled on a cold drum to form a cast sheet, which becomes a thick sheet with an A / B / C three-layer structure. The cold drum temperature is 25-35°C; the die lip opening is set at 2-4 mm.
[0043] (4) The casting sheet enters the longitudinal drawing from the longitudinal drawing entrance, is longitudinally stretched after preheating, and is cooled by the cooling roller to form a unidirectional sheet. The casting sheet speed is set at 5-70 m / min, the preheating roller temperature is set at 60-90 °C, the stretching roller pressure is set at 2-8 kg, the stretching temperature is set at 70-130 °C, the infrared power is 40-60%, the longitudinal stretching ratio is 2.0-3.8, and the cooling roller temperature after stretching is set at 20-40 °C; (5) The unidirectional sheet enters the horizontal stretch through the horizontal zipper clamp, and forms an optical grade polyester base film after horizontal preheating, horizontal stretching, shaping and cooling; the horizontal zipper clamp speed is 150~250m / min, the preheating section temperature is set at 100~130℃, the stretching section stretching temperature is 110~150℃, the stretching ratio is 3.0~4.5 times, the heat setting section shaping temperature is set at 220~245℃, and the cooling temperature is set at 20~40℃.
[0044] (6) After horizontal stretching, the polyester base film enters the traction process for corona, thickness measurement, defect detection, etc. and is rolled up by the winding device.
[0045] (7) The reeled mother roll enters the slitting device for slitting, with a slitting speed of 300~500m / min.
[0046] Table 6 is the performance table of the prepared high-definition transparent optical grade polyester film:
[0047] The high-definition, transparent optical-grade polyester films prepared by the above Examples 1-1, 1-3, 1-5, and 1-6 have a light transmittance of more than 90%, a haze of less than 0.8%, a clarity of more than 99.8%, and a clarity grade of A under strong light.
[0048] Note: T / %: Transmittance is the percentage of the luminous flux passing through a transparent or translucent body to its incident luminous flux; H / %: Haze, which is the percentage of the transmitted light intensity that deviates from the incident light by more than 2.5° to the total transmitted light intensity; C / %: Clarity, which is the degree of obstruction caused by particles in a transparent or translucent body to the transmission of light; Clarity under strong light: A: No fog or whitish under strong light or sunlight; B: Slight fog or whitish under strong light or sunlight, the number of fog is ≤30 / 10*10cm, or slightly whitish; C: Moderate fog or whitish under strong light or sunlight, the number of fog is ≤100 / 10*10cm, or moderately whitish; D: Moderate fog or whitish under strong light or sunlight, the number of fog is ≤200 / 10*10cm, or moderately whitish; Ordinary antiblocking agent products refer to masterbatch slices of inorganic particles with an average particle size of 1~5um that exist on the market.
[0049] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A method for preparing an ultra-clear optical grade polyester film, characterized in that: The steps include: S1: preparing polyethylene terephthalate, adding terephthalic acid, ethylene glycol and various additives into an esterification reaction kettle to prepare dihydroxyethyl terephthalate, and adding modified monomers into the esterification reaction kettle, and then preparing polyethylene terephthalate through esterification and polycondensation reaction to obtain optical grade polyethylene terephthalate slices, wherein the intrinsic viscosity of the polyethylene terephthalate slices is 0.60-0.75 dL / g, the melting point is 240-260°C, the mass fraction of diethylene glycol is 1-3%, and the terminal carboxyl content is 15-30 mol / t; S2: preparing an optical-grade nano-scale opening agent, selecting special particles and grinding them to obtain nano-scale particles, and then mixing them with a solvent to prepare a slurry, adding the prepared slurry into an esterification reactor, and adding a modified monomer into the esterification reactor, and granulating the nano-scale opening agent through esterification polymerization, wherein the nano-scale opening agent has an intrinsic viscosity of 0.60-0.75 dL / g, a melting point of 250-270°C, an L value of 30-80, a b value of 0-5, and a terminal carboxyl content of 15-30 mol / t; S3: The polyethylene terephthalate slices prepared in step S1 are sent to a vacuum hopper for dust removal, then to a static mixer, and then to a main extruder for melt extrusion at 265-295° C. to serve as an intermediate layer B for standby use; S4: sending the polyethylene terephthalate slices prepared in step S1 and the mixture of the nano-scale opening agent prepared in step S2 to two auxiliary extruders respectively, and performing melt extrusion at 265-295° C., wherein the material extruded by one auxiliary extruder is used as the upper surface layer A for standby use, and the material extruded by the other auxiliary extruder is used as the lower surface layer C for standby use; S5: passing the prepared middle layer B, upper surface layer A and lower surface layer C through a co-extrusion die, extruding them together through the die, and rapidly cooling them on a cold drum to form a cast sheet, which becomes a thick sheet with a three-layer structure of A / B / C. The cold drum temperature is 25-35° C., and the die lip opening of the co-extrusion die is set at 2-4 mm; S6: The casting sheet enters the longitudinal drawing machine from the longitudinal drawing entrance, is longitudinally stretched after preheating, and is cooled by the cooling roller to form a unidirectional sheet. The conveying speed of the casting sheet is set at 5-70 m / min, the temperature of the preheating roller is set at 60-90°C, the stretching roller pressure of the longitudinal drawing machine is set at 2-8 kg, the stretching temperature of the longitudinal drawing machine is set at 70-130°C, the infrared power of the longitudinal drawing machine is 40-60%, the longitudinal stretching ratio is 2.0-3.8, and the temperature of the cooling roller is set at 20-40°C; S7: The unidirectional sheet enters the horizontal stretching machine through the horizontal zipper clamp, and forms an optical-grade polyester base film after horizontal stretching preheating, horizontal stretching, shaping, and cooling. The conveying speed of the horizontal zipper clamp is 150-250 m / min, the temperature of the preheating section of the horizontal stretching machine is set at 100-130°C, the stretching temperature of the stretching section of the horizontal stretching machine is 110-150°C, the stretching ratio of the horizontal stretching machine is 3.0-4.5 times, the shaping temperature of the heat shaping section of the horizontal stretching machine is set at 220-245°C, and the cooling temperature of the horizontal stretching machine is set at 20-40°C; S8: After being horizontally stretched, the polyester base film enters the traction process for corona, thickness measurement, and defect detection, and is rolled up by a winding device to form a polyester base film mother roll; S9: The wound polyester base film mother roll enters the slitting device for slitting at a slitting speed of 300 to 500 m / min to obtain the ultra-clear optical grade polyester film.
2. The method for preparing the ultra-clear optical grade polyester film according to claim 1, characterized in that: In step S1, the various types of additives include one or more of a catalyst, a stabilizer, an antioxidant, a toner, an anti-ether agent, and a stabilizer; The catalyst is one or more of antimony trioxide, antimony glycol, aluminum trioxide, Ti series, germanium series, tin series, and cobalt series; The stabilizer is one or more of phosphoric acid, phosphorous acid, triphenyl phosphate, and triphenyl phosphite; The antioxidant is one or more of the hindered phenol antioxidants CHEMNOX1010, CHEMNOX1076, CHEMNOX1098, and CHEMNOXDLTP; The modified monomer is one or a combination of isophthalic acid and benzoate, and the added ratio of the modified monomer is 1-10% of the total mass.
3. The method for preparing the ultra-clear optical grade polyester film according to claim 1, characterized in that: In step S2, the special particles are one or more of silicon dioxide, silica gel fine powder, silicon microspheres, calcium carbonate, calcium sulfate, barium carbonate, barium sulfate, and hydrated magnesium silicate; The average diameter of the particles in the slurry is one or more of 20nm, 50nm, 100nm, 150nm, 200nm, 220nm, and 300nm; The shape of the particles in the slurry is one or more of spherical, columnar, rhombic, and amorphous; The ratio of particles to solvent in the slurry is: 0 to 100 parts by mass of inorganic particles mixed with 0 to 1000 parts by mass of solvent; The nano-scale opening agent is composed of 1% to 25% by mass of nano-slurry and 99% to 75% of copolyester with a molecular weight of 20,000 to 30,000; The modified monomer is an aliphatic diol comonomer, one or more of 1,3-propylene glycol, 1,4-butylene glycol, and 1,6-hexanediol, and the modified monomer accounts for 2-4% of the solvent in the reactor.
4. The method for preparing the ultra-clear optical grade polyester film according to claim 1, characterized in that: The main extruder and the auxiliary extruder are both twin-screw extruders, and the twin-screw extruder is also equipped with a vacuum device, and the vacuum degree of the vacuum device is set to -10 to 4 bar.
5. The method for preparing the ultra-clear optical grade polyester film according to claim 1, characterized in that: The mixed material in the auxiliary extruder is composed of 95% to 50% by mass of polyethylene terephthalate slices and 5% to 50% by mass of nano-level opening agent.
6. The method for preparing the ultra-clear optical grade polyester film according to claim 1, characterized in that: In the step S6, the longitudinal stretching machine is composed of three parts: a preheating roller group, a stretching roller group, and a cooling roller group, wherein each roller of the preheating roller group is made of one or more of chrome-plated rollers, tungsten carbide, and aluminum oxide materials, and is driven by a motor; the stretching roller group is composed of three groups of stretching rollers, and infrared radiators are installed on the first two groups, and the rollers of the stretching group are made of one or more of chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor; the rollers of the cooling group are made of one or more of chrome-plated rollers, tungsten carbide, aluminum oxide, and ceramic materials, and are driven by a motor; The longitudinal stretching adopts a three-point stretching method. The temperature of the first stretching is 70-90°C, infrared heating is set, and the stretching ratio is between 1.0 and 1.2; the temperature of the second stretching is 90-100°C, infrared heating is set, and the stretching ratio is between 1.2 and 1.7; the temperature of the third stretching is 100-130°C, without infrared heating, and the stretching ratio is between 1.7 and 2.
Citation Information
Patent Citations
Low-haze polyester film and preparation method thereof
CN114771070A
Cited By
Preparation method of transparent cake support
CN120862802A
Method for preparing a transparent cake holder
CN120862802B